Back to Solidarity-Based Living? The Economic Crisis and the Development of Alternative Projects in Portugal - Baumgarten, Britta (PARTECIPAZIONE E CONFLITTO, 2017)
The socio-economic crisis in 2011 caused a decrease in living standards for a large part of the Portuguese population, especially after the implementation of a new austerity programme. At the same time the country saw an increase in alternative projects such as: self-organised cultural centres; urban gardening groups; and solidarity-based exchange networks. The main aim of this contribution is to analyse how the crisis impacted these projects in Portugal in cities and also rural areas. The argument that the crisis had an adverse effect on resilience projects is strengthened by the results of case studies in other countries affected by the crisis and by empirical observations regarding the case of Portugal. After having reviewed the scarce literature on social resilience and alternative projects I present data from an analysis of internet pages and a questionnaire on the impact of the socio-economic crisis on the projects of Rede Convergir in 2015.